Pengaruh Disiplin Kerja dan Kompensasi terhadap Kinerja dengan Kepuasan Kerja sebagai Mediator pada Karyawan PT. X di Kab. Bekasi - Arianty, Desy; Yullyanti, Riskah; Dewi, Mega Sinta; Saputra, Dwiky (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the mediating effect of job satisfaction in the relationship between work discipline and compensation on employee performance. This study uses quantitative research and uses a questionnaire as a data collection method. The population was 30 people, the research sample was 30 people with the census method. The research analysis method uses the t test, F test, simple and multiple linear regression analysis and path analysis. The results of this study indicate that work discipline and compensation affect employee performance. Work discipline and compensation affect employee satisfaction and job satisfaction can mediate discipline and compensation on employee performance. Keywords: Compensation, Employee Performance, Job Satisfaction, Work Discipline.